2022
DOI: 10.1002/sia.7128
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of Au/Cr bilayer thin films using combined X‐ray reflectivity and grazing incidence X‐ray fluorescence measurements

Abstract: Gold thin‐film mirrors are widely used as X‐ray reflective optics to manipulate X‐rays especially in synchrotron beamlines. Application of a thin underlying buffer layer of chromium enhances the adhesion of gold film to the substrate material and provides long term structural stability. In the present work, Au/Cr bilayers deposited using the DC magnetron sputtering technique with different thickness values on a Si substrate are studied to better understand the correlation between micro‐structure properties and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The combination of GI-XRF spectrometry and XRR with GI-XRD applied to Au/Cr bilayers showed 60 that relatively large residual stress existed in the gold layer when the chromium layer was small. The authors concluded that mechanically stable Au/Cr bilayer systems can be produced if the thickness of the chromium binder layer was about 100 Å.…”
Section: Grazing X-ray Techniques Including Txrf Spectrometrymentioning
confidence: 99%
“…The combination of GI-XRF spectrometry and XRR with GI-XRD applied to Au/Cr bilayers showed 60 that relatively large residual stress existed in the gold layer when the chromium layer was small. The authors concluded that mechanically stable Au/Cr bilayer systems can be produced if the thickness of the chromium binder layer was about 100 Å.…”
Section: Grazing X-ray Techniques Including Txrf Spectrometrymentioning
confidence: 99%